Rational Speculative Bubbles in the Fine Wine Investment Market - Czupryna, Marcin; Oleksy, Paweł (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The paper focuses on detection of rational speculative bubbles in fine wineinvestment market. Our research was conducted using recursive tests. The chosenmethod additionally allowed us to set time frames for potential bubbles. Theresults have shown that speculative bubble episodes appeared between 2006–2007both in fine wine market and in most of selected traditional stock exchanges.However, only the fine wine market recorded the second wave of speculativebubbles between 2010–2011.